Protective effect of Mumiju against acetic acid-induced ulcerative colitis in rats - Nadar Shahrokhi; Zakieh Keshavarzi; Mohammad Khaksari Haddad; Fereshteh Amirafzali; Shahriar Dabiri; Nava Shahrokhi (Mashhad University of Medical Sciences, 2018)
Objective: In this study, we elucidated the ameliorative effect of aqueous extract of leaves of Mumiju against acetic acid-induced experimental colitis in male rats. Materials and Methods: The animals were randomly divided into four groups (n=7) including I: control group, II: vehicle group (injected with 2 ml acetic acid (4%) intra rectally), III and IV: treatment groups which received Mumiju (250 mg/kg) orally or intraperitoneally for 4 consecutive days after ulcer induction. Ulcer index, severity of inflammation, colonic levels of superoxide dismutase (SOD), glutathione (GSH), and malondialdehyde (MDA), and histological changes were recorded after the treatment regimen of 4 days. Results: The ulcer index, severity of inflammation and colonic MDA levels were increased following intrarectal instillation of acetic acid. Also, acetic acid significantly decreased the SOD and GSH levels. Treatment with Mumiju for 4 days exhibited significantly lowered oxidative stress, while elevated of SOD and GSH levels. Regenerative-healing patterns also was seen by histopathological findings after treatment with Mumiju. Conclusion: The present investigation demonstrates that Mumiju could be regarded as a herb with potent therapeutic value in the amelioration of experimental colitis in laboratory animals by modulation of oxidant- antioxidant system.